Statistical properties of spectra of chloronaphthalenes - Bielinska-Waz, Dorota; Waz, Piotr; Clark, Timothy; Puzyn, Tomasz; Peplowski, Lukasz; Nowak, Wieslaw (Journal of Mathematical Chemistry, 2013)
We introduce spectral density distribution moments as molecular descriptors. We demonstrate that these descriptors correctly represent the molecular structure. To prove the correctness of the new descriptors, we consider the IR spectra of 76 chloronaphthalenes. We show that the consecutive substitutions of the hydrogen atoms by the chlorine atoms are reflected by a regular behavior of the descriptors and, consequently, that the descriptors may be used to construct classification diagrams. The diagrams allow for a clear distinction between the compounds containing different numbers of the substituents. In the diagrams, symbols corresponding to the isomers with a given number of chlorine atoms nearly overlap and form clusters. The clusters corresponding to different numbers of chlorine atoms are well separated and distributed in a regular way. The same kind of analysis we also use as a tool for checking the correctness of the calculated spectra.
Keywords: Statistical spectroscopy; Descriptors; Molecular similarity; DFT methods